Growth of InN ultrathin films on AlN for the application to field-effect transistors - Dayeon Jeong; Atsushi Kobayashi; Kohei Ueno; Hiroshi Fujioka (AIP Advances, 2020)
Herein, we report the growth method of ultrathin indium nitride (InN) films on aluminum nitride (AlN) templates by sputtering and its application to field-effect transistors (FETs). Although island-like InN surfaces were formed at the initial film growth stage, the height of the islands on the surface could be controlled by changing the growth temperature. The height of the InN islands grown at 500 °C was lower than those grown at 440 °C and 480 °C. To demonstrate an application of the InN/AlN heterostructure to FETs, we fabricated FETs using a 2-nm-thick InN film grown on an AlN template. The FET with the InN channel grown at 500 °C exhibited a drain current density of 0.19 mA/mm and an on/off ratio of approximately 102 although the drain current of the FET with the InN grown at 450 °C was not adequately controlled by the gate bias. These results indicate that the growth condition of InN films is responsible for the characteristics of InN/AlN FETs.